Repurposing the Medicines for Malaria Venture’s COVID Box to discover potent inhibitors of Toxoplasma gondii, and in vivo efficacy evaluation of almitrine bismesylate (MMV1804175) in chronically infected mice - dos Santos, Bruna Ramos; Ramos, Amanda Bruno da Silva Bellini; de Menezes, Renata Priscila Barros; Scotti, Marcus Tullius; Colombo, Fábio Antônio; Marques, Marcos José; Reimão, Juliana Quero (PLOS ONE, 2023)
Toxoplasmosis, caused by the obligate intracellular parasite Toxoplasma gondii, affects about one-third of the world’s population and can cause severe congenital, neurological and ocular issues. Current treatment options are limited, and there are no human vaccines available to prevent transmission. Drug repurposing has been effective in identifying anti-T. gondii drugs. In this study, the screening of the COVID Box, a compilation of 160 compounds provided by the "Medicines for Malaria Venture" organization, was conducted to explore its potential for repurposing drugs to combat toxoplasmosis. The objective of the present work was to evaluate the compounds’ ability to inhibit T. gondii tachyzoite growth, assess their cytotoxicity against human cells, examine their absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties, and investigate the potential of one candidate drug through an experimental chronic model of toxoplasmosis. Early screening identified 29 compounds that could inhibit T. gondii survival by over 80% while keeping human cell survival up to 50% at a concentration of 1 μM. The Half Effective Concentrations (EC50) of these compounds ranged from 0.04 to 0.92 μM, while the Half Cytotoxic Concentrations (CC50) ranged from 2.48 to over 50 μM. Almitrine was chosen for further evaluation due to its favorable characteristics, including anti-T. gondii activity at nanomolar concentrations, low cytotoxicity, and ADMET properties. Administering almitrine bismesylate (Vectarion®) orally at dose of 25 mg/kg/day for ten consecutive days resulted in a statistically significant (p < 0.001) reduction in parasite burden in the brains of mice chronically infected with T. gondii (ME49 strain). This was determined by quantifying the RNA of living parasites using real-time PCR. The presented results suggest that almitrine may be a promising drug candidate for additional experimental studies on toxoplasmosis and provide further evidence of the potential of the MMV collections as a valuable source of drugs to be repositioned for infectious diseases.